1997
DOI: 10.1017/s0305004196001399
|View full text |Cite
|
Sign up to set email alerts
|

On the notion of Jacobi polynomials for codes

Abstract: In this paper, we introduce the notion of Jacobi polynomials for codes, and establish some fundamental features of it. This notion comes out of considerations on the various invariants of the codes (e.g. [22–24]); it has to do with Jacobi theta-series of positive definite quadratic forms (cf. [9], p. 82). Thus the name ‘Jacobi polynomials for codes’ traces this fact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…We regard these binary vectors as the characteristic vectors for the 2 elements subsets in an eight elements set. We naturally arrive at a Johnson scheme J (8,2). This scheme consists of all the 2-elements subsets in an eight elements set X.…”
Section: Hamming Association Subschemes In Rm(1 3)mentioning
confidence: 99%
See 3 more Smart Citations
“…We regard these binary vectors as the characteristic vectors for the 2 elements subsets in an eight elements set. We naturally arrive at a Johnson scheme J (8,2). This scheme consists of all the 2-elements subsets in an eight elements set X.…”
Section: Hamming Association Subschemes In Rm(1 3)mentioning
confidence: 99%
“…Two elements subsets x and y of X are connected by the hth relation R h (0 ≤ h ≤ 2) if and only if the condition |x ∩ y| = 2 − h holds. To each deep hole v we correspond the 2 elements setv consisting of non-zero coordinate positions of v. It can be observed that the mapping v →v is a bijection between the set of all deep holes for RM (1,3) and J (8,2). Further it holds that…”
Section: Hamming Association Subschemes In Rm(1 3)mentioning
confidence: 99%
See 2 more Smart Citations
“…Ozeki [42] or Runge [43]) that if we take the index 2 subgroup H (of order 96) of G defined by The important implication of this fact is that we can understand the space of modular forms completely through the invariant ring of the finite group H. Interestingly enough, this situation can be generalized in several directions. We list some of them in the following table.…”
Section: Definition (Weight Enumerator Of a Code) -For A Code C Thementioning
confidence: 99%